Management of Anterior Cruciate Ligament Injuries in Children and Adolescents: A Systematic Review - Hongfu Jin; Nouman Tahir; Shide Jiang; Herasimenka Mikhail; Volotovski Pavel; Masoud Rahmati; Seung Won Lee; Wenfeng Xiao; Yusheng Li (Sports Medicine - Open)
Abstract Background Due to rising sports participation, anterior cruciate ligament (ACL) tears are increasingly prevalent in children and adolescents. This systematic review aimed to evaluate and summarize the management strategies for ACL injuries in children and adolescents. Methods A comprehensive search of PubMed, Embase, Web of Science, and Cochrane Library databases was conducted to identify studies reporting outcomes of ACL injuries in children and adolescents. Key outcomes were synthesized descriptively, including knee instability, secondary damage, growth disturbances, and return-to-sport (RTS) rates. Results A total of 7,507 publications were initially screened, with 105 studies involving 8294 children or adolescents satisfying the inclusion criteria. Conservative treatments were associated with elevated rates of knee instability (35.85-100%), secondary meniscal and cartilage damage, and long-term degenerative changes. Conversely, surgical interventions, including physeal-sparing and transphyseal techniques, demonstrated superior outcomes with lower instability rates (0-7.41%), fewer complications, and higher RTS rates (83.4-92.6%). Pooled RTS rates for conservative treatments were 44.0% (95%CI: 0.018–0.927), while physeal-sparing ACL reconstruction showed a pooled RTS rate of 92.6% (95%CI: 0.732-1.000) and transphyseal ACL reconstruction reported an RTS rate of 83.4% (95%CI: 0.722–0.924). Conclusion Conservative management of ACL injuries in children and adolescents is linked to higher rates of knee instability, secondary meniscal and cartilage damage, and degenerative changes. In contrast, surgical interventions, such as physeal-sparing and transphyseal techniques, yield better outcomes in knee stability, complications reduction, and RTS rates. However, risks such as graft rupture, repeat surgeries, and potential growth disturbances emphasize the importance of tailoring surgical approaches to the patient’s growth stage and anatomical characteristics.